Test Anxiety and the Americans With Disabilities Act. (September 2017) - Lovett, Benjamin J.; Nelson, Jason M.
Test anxiety leads to requests for accommodations under the Americans With Disabilities Act (ADA), but many testing entities have expressed skepticism about whether test anxiety qualifies as a disability. This article addresses three legal issues raised by the inclusion of test anxiety under ADA: whether test anxiety is a mental impairment, whether test-taking is a major life activity, and whether test anxiety substantially limits test-taking. The article then turns to questions of policy: How should ADA claims for test anxiety be handled by educational institutions, independent testing agencies, and employers? A review of scientific research and legal authorities are used to answer these questions. Most individuals with high test anxiety levels will not qualify as disabled under ADA, although there will be exceptions to that general rule, and testing entities should always conduct an individualized inquiry into each claim.